Commercial hunting in Central Africa : a threat for the biodiversity or a sustainable economic activity ? : The case of Central African Republic - (:unkn) unknown (My University, 2013)
In central Africa, commercial hunting strongly contributes to the protein supply of rural and urban households. It is accused of wildlife resources overexploitation, with very negative impacts on animal biodiversity and forest regeneration and with important risks of emergent diseases development. From the Central African Republic case, we want to show that: commercial hunting has a long history, which begins with European colonization and goes on until today, without breaking, but with different actors ; takings mainly focuse small and medium wildlife which naturally has very strong dynamics of reproduction and which supports high pressures of hunting; Bushmeat, especially smoked meat, plays an important part for food safety of rural and urban poorest; distribution of this food products involves various actors of informal economy; this sector is illegal, but never criminal; bushmeat is not in open access, but the network is strongly controlled by social, economic, geographical and technical constraints. From these reports, we propose a new policy approach to wildlife management in central Africa, favoring an adaptive management of common fauna based on village territory, focusing State on its kingly functions to organize proteinic food safety for all people and orientating research towards small fauna biology and local communities technical support.
Keywords: African Research